The Link Between Firms? Innovation Decision and the Business Cycle: An Empirical Analysis - Diana Heger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
The sensitivity of innovation activities with respect to the business cycle is often assumed to be small. In this paper the hypothesis on cyclical dependence of innovation activities is tested for firms in the German manufacturing, and additionally for SMEs. To this end firms? innovation decisions are considered. The decision to innovate in one period is modelled via a first-order Markov chain approach. The results suggest that the patterns in innovative behavior are linked to the business cycle.
Keywords: L6; D21; O31; C23; C25; 330; Innovation; Business Cycle; Panel Model; Markov Chains; Innovationsmanagement; Innovation; Konjunktur; Klein- und Mittelunternehmen; Schätzung; Deutschland